Student Responses to the Implementation of Google Site-Based Learning Media in Vocational High Schools on the Material of Sequences and Series - Indrasari, Peti; Latifa, Ulfa; Pramuditya, Amami Surya (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research aims to determine students' responses to the implementation of Google Sites-based learning media at a vocational school in Cirebon Regency on the topic of sequences and series. Based on interviews with teachers, there are still difficulties in delivering the learning material, indicating the need for learning media that can facilitate teachers in presenting the content. Google Sites was chosen as the learning medium due to its ease of access and its ability to present various types of interactive learning content. The methods and models used in this research are Research & Development (R&D) and the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. The technique employed involves administering a response questionnaire to 21 respondents from the tenth grade. During the analysis phase, field observations were conducted to identify the needs for learning media, followed by determining the material and creating the media according to the planned design, which was then implemented to gather students' responses to the use of the learning media. The evaluation stage of this research utilized data from suggestions and feedback during the implementation. The results indicate that 76.2% of respondents found this learning media to be very beneficial, and 57.1% considered it very engaging. The features that were most helpful in the learning process were the materials and instructional videos. In conclusion, Google Sites has proven to facilitate both teachers and students in learning the topic of sequences and series; however, some students still experience difficulties in understanding the material, indicating the need for additional direct explanations from the teacher.